The Effect of School Capacity and Teacher Capacity on Student Experience in Using Digital Devices: A Comparative Study in Thailand and Taiwan - Bui, Nguyen-Bich-Thy; Romi Aswandi Sinaga; Arsairach, Suphannee (Alberta Journal of Educational Research, 2023)
This study aimed to compare the levels and relationships between school capacity, teacher capacity, and student experience in Thailand and Taiwan. Moreover, school types and school locations were examined to explore these differences. The secondary data from PISA 2018 were analyzed by quantitative approach. The results revealed that only school types had differences in teacher capacity in Thailand, whereas other demographic information did not. Other results showed different directions of correlations between school capacity, teacher capacity, and student experience. School capacity in both countries was able to predict teacher capacity. Other factors as predictors of the student experience are recommended. Keywords: comparative study, digital learning, school capacity, student experience, teacher capacity Cette étude visait à comparer les niveaux et les relations entre la capacité des écoles, la capacité des enseignants et l'expérience des étudiants en Thaïlande et à Taïwan. En outre, les types d'écoles et les lieux d'enseignement ont été examinés pour explorer ces différences. Les données secondaires de PISA 2018 ont été analysées en employant une approche quantitative. Les résultats ont révélé que seuls les types d'écoles étaient associés aux différences dans la capacité des enseignants en Thaïlande, alors que les autres informations démographiques ne l’étaient pas. D'autres résultats ont montré différents types de corrélations entre la capacité des écoles, la capacité des enseignants et l'expérience des élèves. Dans les deux pays, la capacité des écoles a permis de prédire la capacité des enseignants. Il est recommandé d'utiliser d'autres facteurs pour prédire l'expérience des élèves. Mots clés : étude comparative, apprentissage numérique, capacité de l'école, expérience de l'élève, capacité de l'enseignant